Menyongsong Era Globalisasi dengan Pelatihan Desain Grafis - Abdulah; Muhimatul Khaerunisa (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2023)
Abstract Competition in this era of globalization is very diverse. Humans must have skills if they want to compete with others. Students are no exception, who are required to be able to adapt to the times. Skills that can be honed and used are graphic design skills. The long-term goal of this graphic design training activity is to produce Brebes students who have knowledge and skills in the field of graphic design, especially using the corel draw application. This service activity is carried out using the mentoring method and providing direct graphic design training. After the speaker explained, he was given the opportunity for discussion and questions and answers. The expected result is to increase the graphic design skills of Brebes students, especially in using the corel draw application. Keywords: Graphic Design, Corel Draw, Creativity